Dampak Boikot Konsumen terhadap Fluktuasi Harga Saham Starbucks: Analisis Empiris - Nurdina, Hana; Akbar, Taufik; Yuda Nugraha, Yongky Rangga (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
This study focuses on the impact of consumer boycotts on Starbucks' stock price fluctuations, employing an in-depth empirical approach to analyze the moderating factors that influence the intensity and duration of such effects. The study provides quantitative data on stock price variations during different boycott periods and explores the roles of macroeconomic conditions, social media sentiment, and mitigation strategies in moderating boycott impacts. Findings indicate that consumer boycotts can significantly trigger stock price volatility, particularly when accompanied by intense media coverage and high social media engagement. Under unstable economic conditions, boycott impacts tend to be more severe and require extended recovery times. Conversely, companies adopting proactive crisis communication approaches and implementing responsive and transparent mitigation strategies are better positioned to expedite stock price recovery. This research contributes to financial and consumer behavior literature by demonstrating that investor perceptions are influenced by public sentiment dynamics, particularly as recorded on social media platforms. Furthermore, the findings highlight the critical importance of crisis and reputation management in the digital era, where rapid, uncontrolled information flow can accelerate the spread of negative sentiment affecting company valuations. These results aim to assist multinational companies in developing more adaptive strategies to address potential consumer boycotts in the future.